1975
DOI: 10.1016/s0022-5347(17)59571-3
|View full text |Cite
|
Sign up to set email alerts
|

Horseshoe Kidneys: A 40-year Experience

Abstract: The results presented show that horseshoe kidney is a non-fatal anomaly of renal development that can be managed successfully by standard urologic procedures. Most clinical problems are caused by hydronephrosis and renal calculi. Careful attention to the anatomy, vasculature and drainage from renal pelves at the time of operation will assure good postoperative results. The Foley Y-V pyeloplasty is a highly effective procedure for relief of ureteropelvic junction obstruction in horseshoe kidneys. As with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
3

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(67 citation statements)
references
References 18 publications
2
62
0
3
Order By: Relevance
“…Again, these success rates are less favorable than for endopyelotomy in orthotopic kidneys, which range from 77 to 89% (15,16) with absent crossing vessels, and less than 70% in the presence of a crossing vessel. The overall radiographic success rate of 78% in this study is thus comparable to success rates reported for open pyeloplasty in horseshoe kidneys (9,10). Smaller series of horseshoe MIS pyeloplasty are limited to cohorts of five or fewer patients, and report success rates ranging from 66% to 100% (1,7,17) ( Table-4).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Again, these success rates are less favorable than for endopyelotomy in orthotopic kidneys, which range from 77 to 89% (15,16) with absent crossing vessels, and less than 70% in the presence of a crossing vessel. The overall radiographic success rate of 78% in this study is thus comparable to success rates reported for open pyeloplasty in horseshoe kidneys (9,10). Smaller series of horseshoe MIS pyeloplasty are limited to cohorts of five or fewer patients, and report success rates ranging from 66% to 100% (1,7,17) ( Table-4).…”
Section: Discussionsupporting
confidence: 82%
“…The largest series to date on pyeloplasty for horseshoe UPJ obstruction report outcomes for open Foley Y-V plasty and they generally lack reporting of both radiologic and clinical follow up which is now standard (9). Nevertheless, open surgery success rates in horseshoe kidneys were less favorable than in orthotopic kidneys, ranging from 55 to 80% (9,10) compared to over 90% respectively (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…3 Even though the horse shoe kidney produces no symptoms, it is frequently concomitant with other vascular or genitourinary anomalies. [5][6][7][8] Therefore, it is important to be aware of these anomalies in clinical practice. Moreover, the horseshoe kidney can be transplanted en bloc or after division of the renal isthmus.…”
Section: Introductionmentioning
confidence: 99%
“…In 20% of the cases with horseshoe kidneys stone formation is seen which is the most frequent indication for surgical intervention. [3,4] During fetal development, if the kidneys do not complete their normal anatomical rotation, pelvis is situated in front of the kidney, and ureter enters into pelvis at a higher level than its normal insertion site leading to the formation of a horseshoe kidney. This anatomical alteration constitutes a risk for formation of renal stones which are refractory to spontaneous passage.…”
Section: Introductionmentioning
confidence: 99%